Study of Economic Growth Through The Environmental Quality Index on The Island of Kalimantan - Vita, Fransiska Prana; Nur, Muhammad Anshar; Sopiana, Yunita (Syntax Corporation, 2025)
This study examines the relationship between economic growth and environmental quality in four provinces on the island of Kalimantan: West Kalimantan, Central Kalimantan, South Kalimantan, and East Kalimantan, during the period from 2013 to 2020. The focus of this research is to analyze the impact of government spending, domestic investment, and labor productivity on the Environmental Quality Index (EQI) and economic growth in each province. The background of this research relates to the issue of sustainable economic development in Kalimantan, which faces significant challenges such as deforestation, pollution, and climate change. While economic growth, reflected by Regional Gross Domestic Product (RGDP), has benefited societal welfare, it has also negatively affected environmental quality. This quantitative study employs panel data regression analysis and path analysis methods to evaluate data on government spending, domestic investment, labor productivity, EQI, and economic growth from 2013 to 2020. The regression results indicate that government spending negatively impacts both EQI and economic growth, while domestic investment and labor productivity positively affect both. Additionally, EQI negatively influences economic growth. Path analysis reveals no indirect effect of government spending, domestic investment, and labor productivity on economic growth through EQI. The findings suggest a negative relationship between economic growth and environmental quality, where increased economic growth tends to decrease environmental quality. This research aims to contribute to policymaking related to sustainable economic development, particularly in balancing economic growth with environmental preservation in Kalimantan. Furthermore, it may serve as a reference for future studies focusing on similar topics.